Antimicrobial Peptides (AMPs) - Sadredinamin, Mehrzad; Mehrnejad, Faramarz; Hosseini, Peyman; Doustdar, Farahnoosh (Novelty in Biomedicine, 2016)
Antimicrobial peptides (AMPs) are extensive group of molecules that produced by variety tissues of invertebrate, plants, and animal species which play an important role in their immunity response. AMPs have different classifications such as; biosynthetic machines, biological sources, biological functions, molecular properties, covalent bonding patterns, three dimensional structures, and molecular targets. These molecules have multidimensional properties including antimicrobial activity, antiviral activity, antifungal activity, anti-parasite activity, biofilm control, antitumor activity, mitogens activity and linking innate to adaptive immunity that making them promising agents for therapeutic drugs. In spite of this advantage of AMPs, their clinical developments have some limitation for commercial development. But some of AMPs are under clinical trials for the therapeutic purpose such as diabetic foot ulcers, different bacterial infections and tissue damage. In this review, we emphasized on the source, structure, multidimensional properties, limitation and therapeutic applications of various antimicrobial peptides.